Intervención fisioterapéutica en paciente de sexo femenino de 3 años con Síndrome de Apert. - Araujo Narváez, Jenipher Jazmín (2024)
The present clinical case of physiotherapy intervention in a 3-year-old female patient with Apert syndrome has the objective of analyzing the effectiveness of the physiotherapy intervention in a patient with Apert Syndrome, under criteria of mobility, balance and muscle strength to know the current quality of life for its effect, the methodology that refers to the type of documentary and applied research, qualitative approach, bibliographic, historical and analytical methods was used, in addition, the observational study techniques and instruments that are evidenced through an observational file where they were obtained results in relation to physiotherapy activities, follow-up and weekly progress of the patient where it was obtained that the scheduled sessions initially correspond to 12 sessions per month, however, the patient was only able to attend 2 per week, 8 sessions where work was done on walking with obstacles and ramps, sensory stimulation with various objectives of colors and textures, exercise on the Bobath ball and passive mobilizations to maintain joint range and greater joint mobilization and muscle strengthening were achieved, which contributed to improving the quality of their physical activity by 20%. life. Therefore, it is advisable to continue with the therapies and verify that you attend all the scheduled sessions and follow up with the corresponding medical unit to know the causes that cause the patient's absence from the 3 scheduled therapies per week by the specialist doctor to achieve greater results by attending all the recommended sessions for the frequent development of the exercises.